Trade in-Game Meat in Jagaraga Village, West Lampung from an Islamic Law Perspective - Sandriansyah, Sandriansyah; Qiftiyah, Maratul (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
This study aims to see the legal status of the game meat trade in Islamic law. This type of research is field research, using observation and interviews with hunters and players who buy and sell game meat. Trading in-game meat must not violate religious and state regulations. This paper finds that hunting and trading animal meat in the field against protected animals is prohibited by Islamic law. Hunting needs to be supervised by those who care so that the ecosystem is well preserved.